Evaluasi Implementasi Kebijakan Publik terhadap Peraturan Daerah Bermasalah - Femmy Silaswaty Faried; Suparwi . (Universitas Islam Balitar, Blitar, 2019)
Evaluation of the implementation of public policy coming out of a regulation of the problematic area, it is possible to study whether a policy that comes out is appropriate for the implementation of a local regulation that has not been And in this case according to researchers is a regional regulation which also goes into problematic category. The problem of the problematic area of the researcher is not only because the regulation of the area is contrary to higher regulations, nor because the local regulation violates the norms of morality, but for researchers Local regulations are also included if the rules are not applicative, so it requires further rules to be applicative to the local regulations.